Crime and Victimization - Baliki, Ghassan (World Bank, Washington, DC, 2013)
Historically, higher crime rates have been associated with higher inequality and poverty. Nevertheless, there remains an ambiguity over the most prominent socioeconomic factors that increase crime rates and individual victimization. This paper discusses victimization and crime rate data collections from the International Crime Victimization Survey (ICVS), the UNODC, and the World Value Surveys (WVS) in an effort to achieve three goals: (1) conduct an assessment on perceptions of public and private insecurity, as well as the fear of victimization; (2) provide a robust cross-regional comparison, where possible, on incidence of crime and evaluate the variability of exposure to victimization across gender and urban and rural residences; and (3) undertake a supplementary regional assessment for Latin America and the Caribbean to match perceptions with actual experience of crime to evaluate the magnitude of the gap in perceived risk of victimization among individuals.